Symptomatic Remission and Counterfactual Reasoning in Schizophrenia - Albacete, Auria; Contreras, Fernando; Bosque, Clara; Gilabert, Ester; Albiach, Ángela; Menchón, José M. (Frontiers in Psychology, 2017)
Counterfactual thinking (CFT) is a type of conditional reasoning involving mental representations of alternatives to past factual events that previous preliminary research has suggested to be impaired in schizophrenia. However, despite the potential impact of these deficits on the functional outcome of these patients, studies examining the role of CFT in this disorder are still few in number. The present study aimed to extent previous results by evaluating CFT in the largest sample to date of schizophrenia patients in symptomatic remission and healthy controls. The relationship with symptomatology, illness duration, and sociodemographic characteristics was also explored. Methods: Seventy-eight schizophrenia patients and 84 healthy controls completed a series of tests that examined the generation of counterfactual thoughts, the influence of the “causal order effect,” and the ability to counterfactually derive inferences by using de Counterfactual Inference Test. Results: Compared with controls, patients generated fewer counterfactual thoughts when faced with a simulated scenario. This deficit was negatively related to scores on all dimensions of the Positive and Negative Syndrome Scale-PANNS, as well as to longer illness duration. The results also showed that schizophrenia patients deviated significantly from the normative pattern when generating inferences from CFT. Conclusions: These findings reveal CFT impairment to be present in schizophrenia even when patients are in symptomatic remission. However, symptomatology and illness duration may have a negative influence on these patients' ability to generate counterfactual thoughts. The results might support the relevance of targeting CFT in future treatment approaches, although further research is needed to better describe the relationship between CFT and both symptomatology and functional outcome.